2019
DOI: 10.1167/19.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of natural images as a function of dynamic range

Abstract: The statistics of real world images have been extensively investigated, but in virtually all cases using only low dynamic range image databases. The few studies that have considered high dynamic range (HDR) images have performed statistical analyses categorizing images as HDR according to their creation technique, and not to the actual dynamic range of the underlying scene. In this study we demonstrate, using a recent HDR dataset of natural images, that the statistics of the image as received at the camera sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This assumption would correspond (going back to the vision fundamentals mentioned in Section 3) to having as input image for our GM framework the signal generated by the photoreceptors. The reason for this is the well known fact that the Naka-Rushton equation that models photoreceptor responses optimizes the performance efficiency of cones and rods by adapting the possibly high dynamic range (HDR) input intensities to the SDR representation capabilities of photoreceptors [70]. In fact several successful tone mapping approaches (that convert HDR images into SDR) in the computer graphics and image processing communities use non-linear curves based on the Naka-Rushton model (e.g.…”
Section: The Hdr Casementioning
confidence: 99%
“…This assumption would correspond (going back to the vision fundamentals mentioned in Section 3) to having as input image for our GM framework the signal generated by the photoreceptors. The reason for this is the well known fact that the Naka-Rushton equation that models photoreceptor responses optimizes the performance efficiency of cones and rods by adapting the possibly high dynamic range (HDR) input intensities to the SDR representation capabilities of photoreceptors [70]. In fact several successful tone mapping approaches (that convert HDR images into SDR) in the computer graphics and image processing communities use non-linear curves based on the Naka-Rushton model (e.g.…”
Section: The Hdr Casementioning
confidence: 99%
“…Once more we have an element that corroborates the efficient coding theory, which is the following. The average luminance histogram of natural images is, in log-log coordinates, piece-wise linear [25], with two lines of different slope at each side of the average level, see Fig. 4 (left).…”
Section: Some Vision Principles Relevant For Hdr Imagingmentioning
confidence: 99%
“…Natural image statistics do change with the dynamic range of the scene, but basic retinal transforms (like photoreceptor response and center-surround inhibition at the level of retinal ganglion cells) have been shown to make the signal statistics almost fully independent of the dynamic range [25]. Indeed, most of the vision literature on dynamic range focused on how objects appear invariant over changing lighting conditions, thus omitting irradiance information [45].…”
Section: Some Vision Principles Relevant For Hdr Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that natural image statistics correlate with perceptual sensitivity and preference (McDermott and Webster, 2012 ; Nascimento et al, 2021 ). Using natural image datasets, the distribution of dynamic range has been characterized (Grimaldi et al, 2019 ), however, the generalization to the chromatic dimension has not been carried out. Moreover, color reproduction does not only concern natural objects, as synthetic scenes generated by computer graphics may also benefit from a larger CGV, although the perceptual gain is not easily quantifiable.…”
Section: Introductionmentioning
confidence: 99%